Voice Disorders in Teachers. A Review - Garcia Martins, Regina Helena [UNESP]; Boia Neves Pereira, Eny Regina [UNESP]; Hidalgo, Caio Bosque [UNESP]; Mendes Tavares, Elaine Lara [UNESP] (Elsevier B.V., 2014)
Introduction. Voice disorders are very prevalent among teachers and consequences are serious. Although the literature is extensive, there are differences in the concepts and methodology related to voice problems; most studies are restricted to analyzing the responses of teachers to questionnaires and only a few studies include vocal assessments and videolaryngoscopic examinations to obtain a definitive diagnosis.Objective. To review demographic studies related to vocal disorders in teachers to analyze the diverse methodologies, the prevalence rates pointed out by the authors, the main risk factors, the most prevalent laryngeal lesions, and the repercussions of dysphonias on professional activities.Materials and Methods. The available literature (from 1997 to 2013) was narratively reviewed based on Medline, PubMed, Lilacs, SciELO, and Cochrane library databases. Excluded were articles that specifically analyzed treatment modalities and those that did not make their abstracts available in those databases. The keywords included were teacher, dysphonia, voice disorders, professional voice.
Keywords: Voice disorders; Teacher; Dysphonia; Professional voice